Oxygen-functionalized soft carbon nanofibers as high-performance cathode of K-ion hybrid capacitor. (June 2020) - Zhang, Chenglin; Xu, Yang; Du, Guangyu; Wu, Yuhan; Li, Yueliang; Zhao, Huaping; Kaiser, Ute; Lei, Yong
Abstract: Facing the calling for the new generation of large-scale energy storage systems that are sustainably low cost based on earth-abundant and renewable elements, the K-ion hybrid capacitor (KIHC) constructed with both carbonaceous cathode and anode will be one of the best choices. By using oxygen-functionalized engineering, we first obtained oxygen-containing soft carbon nanofibers (ONC) cathodes which delivered a high reversible capacity of 130 mA h g −1 over 200 cycles at a current density of 50 mA g −1 within a high voltage window. Even at 5.0 A g −1, a practical capacity of 68 mA h g −1 maintained. The surface-controlled reaction domination instead of diffusion-controlled reaction domination was proposed to harvest high capacitance performance. This storage model effectively overcomes the sluggish properties of storing large-sized K-ions by a diffusion-controlled reaction in conventional cathodes in K-ion batteries (KIBs). The rational design of oxygen functionalization towards approaching more and stable active sites was highlighted. Moreover, a renewable and low-cost full KIHC was configurated by carbonaceous cathode and anode derived from a single carbon source. Graphical abstract: Image 1 Highlights: The carbon nanofibers with high-content –C=O were obtained by an efficient oxygen functionalization engineering. The carbon cathode exhibited great capability of potassium-ion storage within a high voltage window. Surface-dominated reaction of –C=O + K + + e ↔ -C-O-K was verified as the major contributor for the ions storage. A "green" potassium-ion hybrid capacitor with both carbon electrodes derived from same precursor was demonstrated.